2021
DOI: 10.1371/journal.ppat.1009272
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome landscape reflects phenotypic differences in Trypanosoma cruzi life forms

Abstract: Trypanosoma cruzi alternates between replicative and nonreplicative life forms, accompanied by a shift in global transcription levels and by changes in the nuclear architecture, the chromatin proteome and histone posttranslational modifications. To gain further insights into the epigenetic regulation that accompanies life form changes, we performed genome-wide high-resolution nucleosome mapping using two T. cruzi life forms (epimastigotes and cellular trypomastigotes). By combining a powerful pipeline that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(70 citation statements)
references
References 74 publications
4
66
0
Order By: Relevance
“…It is well known that global transcription levels are decreased in TCTs in relation to epimastigote forms [25], and similar findings have been found in T. brucei [53,54]. Recently, we observed that dSSRs in TCTs have more nucleosomes, which are less dynamic than those from epimastigote forms [27]. Here, we detect that H2B.V is predominantly located at dSSRs of epimastigotes but very few H2B.V enrichment peaks were found on TCTs’ genome.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…It is well known that global transcription levels are decreased in TCTs in relation to epimastigote forms [25], and similar findings have been found in T. brucei [53,54]. Recently, we observed that dSSRs in TCTs have more nucleosomes, which are less dynamic than those from epimastigote forms [27]. Here, we detect that H2B.V is predominantly located at dSSRs of epimastigotes but very few H2B.V enrichment peaks were found on TCTs’ genome.…”
Section: Discussionsupporting
confidence: 69%
“…We hypothesized that either H2B.V was spread along the TCT genome or weakly bound to TCT chromatin in comparison to epimastigotes. Nucleosomes harboring H2B.V-H2A.Z are less stable than canonical nucleosomes [12], and their absence could (partially) explain why dSSRs of TCTs were more occupied by nucleosomes than epimastigotes [27]. We speculate that the absence of histone variants would result in a more stable chromatin structure around dSSRs that, in turn, could hamper RNA Pol II binding, likely explaining the decreased global levels of transcription in this life form [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is suspected to be due to the unique characteristic of its histone H1, which lacks the globular domains typically present in other eukaryotes (Toro and Galanti, 1988). Besides, the infective and non-infective parasite life forms display different levels of chromatin condensation during interphase (Hecker and Gander, 1985), differential susceptibility to DNaseI (Spadiliero et al, 2002) and some differences in the nucleosome landscape (Lima et al, 2021). Additionally, the histones of trypanosomes are the least conserved among all eukaryotic histones studied so far, differing from other organisms in size, sequence, and charge (Toro and Galanti, 1988; Thatcher and Gorovsky, 1994).…”
Section: Introductionmentioning
confidence: 99%